Effects of the Dictogloss Method in Teaching Listening Skills to Students - Muhaiminah Akib; Dian Saputra (Universitas Muhammadiyah Sorong, 2019)
The purpose of this study was to investigate the effect of the dictogloss method in teaching listening to students' listening skills. This research was designed as a quasi-experimental. This study aims to investigate whether a material or treatment yields a different outcome for participants. There are two classes in this study, namely the experimental class (which is a sample to be treated with the dictogloss method) and the control class (using a method other than dictogloss). The results of this study are the results of data analysis showing that the results of learning skills in listening to the experimental group obtained the average value for the initial test of 60.33 and 71 for the final test score. While the control group using conventional methods has a mean value for the initial test of 60.1 and 70 for the final test. T test results also indicate that the significance value is 0,000. The significance value states smaller 0.05, it can be stated that Ha is accepted and Ho is rejected, which means that there is an influence of the dictogloss method in improving listening skills in students